Influencia del entorno familiar en el rendimiento académico de niños y niñas del 4to grado de la I.E. Santísimo Sacramento – la Esperanza. - Vergaray Bazan, Diana Eulalia (2018)
The present investigation was carried out with the objective of identifying the influence of the family environment on the academic performance of the children of the 4th grade of the I.E. Blessed Sacrament of the district of Hope. We consider that the participation of parents in the educational process and their academic performance is one of the main factors that contribute to the academic performance of the student and the development of values in integral formation. In the present investigation, 30 students participated in the compilation of information, applying the family social climate scale (FES), which is divided into three dimensions; relationships, development and stability, which are a perceptual and individual measure of the family environment. The minutes of the students were also used, through which we can see the results of the same. The results indicate a significant relationship between one of the aspects of the family climate related to the academic performance of the students. Undoubtedly, the family environment of the people that make it up according to the links that are generated there. A child born into a family of very limited economic resources, with absent parents, without proper care, will have an environment that will not help in the formation of their personality, on the other hand if they grow up in an environment where the first partner -emotional links are provided in an adequate way, providing the basis of security that children need to explore the world around them and for the development of their subsequent interpersonal relationships, we can bet that they will be children with security and values by society, that is, it will grow and be formed with positive attitudes towards life.